МОНГОЛ ДАХЬ ПАРЛАМЕНТЫН ХЯНАЛТЫН АСУУДАЛ - Х.Батхүү; С.Базарпүрэв (Politology, 2023)
One of the legislative power or its significant element is a parliamentary oversight issue and the implementation is being implemented in various methods or forms depending on the state governance form, economic, and democracy index. Monitoring an institution for executive power from parliament is based on a mutual monitoring principle for the theory of sovereignty and conformed with them. Therefore, the research paper has determined the current state of parliamentary oversight in Mongolia, the implementation forms, and readjustments as well as studied a legal framework for implementation, potential, and the political state. Improving the parliamentary oversight effects and accomplishing the methods or the mechanism is to be significant results for the parliamentary autonomy and the parliamentary democracy. Key words: legislative power, parliament, oversight, monitoring, and opposition